Caphosol for prevention of oral mucositis in pediatric myeloablative haematopoietic cell transplantation - Treister, Nathaniel (Br J Cancer, 2017)
BACKGROUND: The primary objective was to determine whether topically administered Caphosol, rinsed orally four times daily at the initiation of conditioning, reduces the duration of severe oral mucositis (OM) compared with placebo among children and adolescents undergoing haematopoietic cell transplantation (HCT). METHODS: This was a Children's Oncology Group multicentre randomised double-blinded placebo-controlled clinical trial. Patients between the ages of 4 and 21 years who were scheduled to undergo myeloablative HCT for any indication were randomised to Caphosol or placebo saline rinses four times daily from initiation of conditioning through day +20. Subjects were assessed daily for OM using the World Health Organisation (WHO) Oral Toxicity Scale, Mouth Pain Categorical Scale (0–10) and the Oral Mucositis Daily Questionnaire (OMDQ). The primary end point was duration of severe OM (WHO ⩾3). RESULTS: The study enrolled 220 participants with a median age of 13.7 years (range 4.0–21.9); 163 (74%) received allogeneic HCT. The mean (±s.d.) duration of severe OM was not reduced among Caphosol (4.5±5.0 days) vs placebo (4.5±4.8; P=0.99) recipients. The incidence of severe OM in the Caphosol and placebo arms was 63% (57 out of 91) and 68% (62 out of 91), respectively (P=0.44). There were no significant differences in any of the secondary end points between the groups. CONCLUSIONS: Caphosol did not reduce severe OM when compared with placebo among children and adolescents undergoing myeloablative HCT. Studies to identify effective interventions for OM are needed in this population.